Public Service Journal About Sharia Pawnshop - Qolbin Salim; Siska Ramadhani Putri; Nasution, Warda Khoiria; Salsabila Meisya Aulia Rahma (FEBI UIN Sunan Kalijaga Yogyakarta, 2023)
This journal is the result of the final report of the final assignment for the Islamic Financial Management course in the form of community service. The form of service that is carried out is by educating the general public about Sharia Pawnshops. This education regarding Sharia Pawnshops is carried out because it turns out that there are still many Indonesian people, especially the Muslim community who do not know about Sharia Pawnshops. Many people still use conventional pawnshops. In fact, when viewed in terms of its products, Pegadaian Syariah has products that are more in line with Islamic Sharia. The purpose of this education is to increase the literacy of the Indonesian people, especially the Muslim community regarding Sharia Pawnshops. In carrying out this service, we use the implementation method which consists of 3 stages. Namely the preparation stage (preparing material to be taught), the stage of making educational media (making posters), and the third is the stage of delivering material (delivered using Instagram media). From this dedication, we made several conclusions, it turns out that the Muslim community in Indonesia still doesn't use it much, even they know about the existence of Sharia Pawnshops and their products.